Concurrent Onset of Pulmonary and Articular Symptoms - Rare Manifestation of Rheumatoid Arthritis Associated Interstitial Lung Disease: A Case Report - Rahim, MA; Parvin, S; Zaman, S; Haque, HF; Rahman, MM; Afroz, SR; Afroze, F; Ahmed, JU; Ahmed, AKMS; Hossain, MD; Rahman, MR; Musa, AKM; et al. (BIRDEM Medical Journal, 2014)
Lung is the most common extra-articular site of involvement in rheumatoid arthritis (RA). It can involve pleura, lung parenchyma and pulmonary vasculature. Among many diseases, most debilitating one is RA associated interstitial lung disease (RA-ILD). Here, we describe a middle aged Bangladeshi lady who presented because of progressively deteriorating non-productive cough, exertional dyspnea and polyarthritis of 5 month duration. Diagnostic workup confirmed RA-ILD and she responded well with prednisolone, hydroxychloroquine and azathioprine. DOI: http://dx.doi.org/10.3329/birdem.v4i1.18554 Birdem Med J 2014; 4(1): 47-49